Anatomical feasibility of an endovascular aortic arch repair with the NEXUS endograft in patients treated with a frozen elephant trunk procedure for aortic arch pathology - Ward Exelmans; Hozan Mufty; Geert Maleux; Peter Verbrugghe; Inge Fourneau (CVIR Endovascular, 2023)
Abstract Background The aim of this study was to evaluate the feasibility of an endovascular repair, using the NEXUS™ Aortic Arch Stent Graft System, in a real-world cohort of patients, treated with a Frozen Elephant Trunk (FET) procedure for pathology involving the aortic arch. Results The preoperative computed tomography angiography scans of 37 patients were retrospectively analyzed using a dedicated workstation. In total, seven patients (N = 7/37; 18.9%) were eligible for endovascular repair. This number increased to eleven patients (N = 11/37; 29.7%) if an additional relining of the distal aorta would be performed. Device suitability was 47.1% in patients (N = 8/17; 47.1%) with aortic arch aneurysm, 12.5% (N = 1/8; 12.5%) in patients with an acute Stanford type A dissection and 50% (N = 2/4; 50%) in patients with Crawford type II thoraco-abdominal aneurysm. The stent graft was not suitable for any of the two patients with chronic type B dissection (N = 0/2; 0%). In 22 patients (N = 22/37; 59.5%) an endovascular repair with this type of stent graft was not feasible due to an inadequate proximal sealing zone. There was no suitable brachiocephalic trunk landing zone in 13 patients (N = 13/37; 35.1%). There was no suitable distal landing zone distal in 14 patients (N = 14/37; 36.8%). This number decreased to ten patients (N = 10/37; 27.0%) when considering an additional relining of the distal aorta. Conclusions Endovascular repair with the NEXUS single branch stent graft is feasible in a minority of this real-world cohort that underwent a Frozen Elephant Trunk procedure. However, the applicability of this device probably improves in cases with isolated aortic arch aneurysms.